To piperidines and beyond - Taylor, CE (2021)
This thesis describes the development of synthetic routes to investigate the relative and absolute stereochemistry of a number of piperidine alkaloids isolated from Microcos Paniculata. This thesis then goes on to explore an intramolecular Diels-Alder reaction, and explores its applicability to natural product synthesis.